Psychological Issues in Amyotrophic Lateral Sclerosis - Gianluca Castelnuovo (Frontiers Research Topics, 2016)
Amyotrophic lateral sclerosis is a fatal and progressive disease, characterized by progressive muscles weakness, with consequent loss of physical capacities. Patients become relentlessly immobile and, in the late stages of the disease, develop a "locked-in" state in which only residual muscular movement is possible, but the intellect and the personality usually remain unimpaired. At now, there is no cure for ALS. The psychological impact of the disease is huge, on both patients and caregivers. Aim of the present Research Topic is to collect new evidence about quality of life, depression, anxiety, pain, spiritual and existential issues, hope and hopelessness in the ALS field, with attention to both patients and their caregivers. Emphasis will be provided to the investigation of psychological support and the possible role of psychologists in this challenging field. Keywords: Amyotrophic Lateral Sclerosis; Health Psychology; Clinical Psychology, Motor Neuron Disorder; Quality of Life. Subtopics: The subtopics to be covered in the Research Topic include, but not limited to: 1. Assessment of psychological variables in ALS 2. Quality of life during the course of the illness 3. Impact of technological assistance to illness (wheelchairs, NIV...) 4. Interfaces among biological, psychosocial, and social factors 5. Psychological and psychotherapeutic interventions 6. Couple and family relationships 7. Research methodology, measurement and statistics 8. Cultural and social features of ALS 9. Professional issues, including training and supervision 10. Implications of research findings for health-related policy